The Role of Applying the Principle of Disclosure and Transparency in Improving the Financial Performance of Commercial Banks in Derna - Mohamed Boualhassia (Journal of Scientific and Human Dimensions, 2026)
This study examines the role of applying the principle of disclosure and transparency in improving the financial performance of commercial banks in Derna, Libya. A descriptive-analytical methodology was adopted, whereby 90 questionnaires were distributed among employees of commercial banks in the city, with 87 valid responses retrieved, yielding a response rate of 96.7%. The findings revealed that the level of disclosure and transparency was high (mean = 4.34), and financial performance was also high (mean = 4.42). Simple regression analysis confirmed a statistically significant effect of disclosure and transparency on financial performance (β = 0.492, p < 0.05), accounting for 16.5% of the variance. Key recommendations include strengthening technological infrastructure, developing human capital, and simplifying banking regulatory frameworks